Effect of Different Edible Coatings on Postharvest Quality of Mandarin Orange (Citrus reticulata Blanco) - Barsha D.C.; Monika Singh; Prakash Khanal; Madan Pandey; Rukmagat Pathak (Universitas Panji Sakti, 2021)
Although Nepal produces a large amount of mandarin it faces huge postharvest losses due to improper postharvest practices. Treating fruits with different edible coatings can minimize postharvest losses. The experiment was carried out in the horticulture lab of Prithu Technical College, Dang, Nepal to evaluate the effects of different edible coating materials on the postharvest quality of mandarin. The experiment was laid in Complete Randomized Design (CRD) with three replications and seven treatments in each replication. Mandarins were coated with different edible coating materials i.e. paraffin wax (100%, 75% and 50%), mustard oil, Aloe vera, turmeric paste and control (non-coated). After coating with different edible materials, mandarins were kept at ambient room conditions (18±2℃ and 52.41±14.35%). The lowest physiological loss in weight at 7, 14and 21 days was recorded in mandarin coated with 75% paraffin wax which was 3.10%, 4.83% and 10.33%, respectively. The highest titratable acidity (0.68%), juice content (46.33%) and marketable fruit percentage (81.73%) were recorded in 75% paraffin wax. The highest total soluble solid (14.00 ˚Brix) was recorded in control. Based on the result obtained from our research, it is suggested to use 75% paraffin wax for the storage of mandarin at ambient room conditions (18±2℃ and 52.41±14.35% RH) as it gives a high percentage of marketable fruits and juice content and also minimizes the physiological loss in weight.